Rabbits, Rabbits, Rabbits: Pet Rabbit Record Book - Joy C. Jordan; Loretta Rodriguez; Jessica Kochert; Bill Heltemes; Chris Decubellis; Renee Gore (EDIS)
Pet rabbits are chosen primarily for their temperment, more so than for their looks. They are generally calm animals that can be easily handled and cared for. In the 4-H Pet Rabbit project (visit http://florida4h.org for more information about this online project), youth learn the skills necessary for choosing a healthy rabbit, proper handling of a rabbit, rabbit health, and general care. This document, the Pet Rabbit Record Book (4H RAR 11), familiarizes youth with the importance of record keeping as an integral part of project management. By tracking inventory, financial records associated with their project, rabbit health and grooming details, and related information, youth will be well prepared to relate their experiences in a written narrative as part of their project completion activities. Original publication date September 2010.